The Divided World : Human Rights and Its Violence - Williams, Randall, 1964- (Book collections on Project MUSE., 2010)
Taking a critical view of a venerated international principle, this book shows how the concept of human rights - often taken for granted as a force for good in the world - corresponds directly with U.S. imperialist aims. Citing internationalists from W.E.B. Du Bois and Frantz Fanon to, more recently, M. Jacqui Alexander and China Mieville, the text insists on a reckoning of human rights with the violence of colonial modernity.